2001
DOI: 10.1039/b102239n
|View full text |Cite
|
Sign up to set email alerts
|

Star-like oriented chromophores

Abstract: The tetrahedral arrangement of perylene bisimide chromophores gives a novel molecular system of antennae for the conversion of di †use solar radiation. A detailed analysis of their UV/Vis spectra gives an impression of the consolidation of the single chromophores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 13 publications
1
19
0
Order By: Relevance
“…The tetrachromophore 37 can be prepared starting from benzoperylenetris-imides 5 by a nucleophilic displacement reaction [106]. Weak exciton interactions were found that cause a reduction of the molar absorptivity of each chromophore; the transition moments of the individual chromophores are tangentially oriented on the surface of a sphere so that the b-transitions become favored.…”
Section: Furthermentioning
confidence: 99%
See 1 more Smart Citation
“…The tetrachromophore 37 can be prepared starting from benzoperylenetris-imides 5 by a nucleophilic displacement reaction [106]. Weak exciton interactions were found that cause a reduction of the molar absorptivity of each chromophore; the transition moments of the individual chromophores are tangentially oriented on the surface of a sphere so that the b-transitions become favored.…”
Section: Furthermentioning
confidence: 99%
“…Thus 4,4',4'',4'''-methanetetrayltetrakis[benzenamine] was, activated as its tetrakis-formamide and the latter condensed with the peryleneimide anhydride 22 to give the tetrachromophore 38 [106]. The peripheral N-atoms of the individual chromophores were substituted by swallowtail substituents to obtain a sufficiently high solubility for spectroscopic investigations.…”
Section: Furthermentioning
confidence: 99%
“…In the case of perylene diimide chromophores, a small redshift of the lowest energy band (ca. 70 cm −1 ) and an enhancement of the molar absorption coefficient was evidenced on going from the monomer to the tetrahedrally arranged molecule 36. This behavior was rationalized on the basis of a peculiar excitonic coupling that was neither J‐ nor H‐like 37…”
Section: Introductionmentioning
confidence: 98%
“…The target TP molecule, namely, tetra-4-[N-(1-Hexylheptyl)perylene-3,4:9,10tetracarboxylicbisimid-N′-yl]phenylmethane, was obtained by a route similar to previous reference, 21 but by direct condensation of four PDI precursors with tetrakis(4aminophenyl)methane in presence of zinc acetate/imidazole rather than by conversion to the tetraformamide. The deposition of isolated TP molecules on metal surfaces is challenging because of its large molecular weight and low thermal stability, making it impossible to transfer by thermal sublimation under ultrahigh vacuum (UHV) conditions.…”
mentioning
confidence: 99%